Progress in the Periodic Mesoporous Organosilicas - Yang, Q.; Liu, Jian; Zhong, H.; Wang, P. (Kexue Chubanshe, 2009)
The integration of organic and inorganic fragments within the pore wall of the periodic mesoporous organosilicas (PMOs) represents one of the recent breakthroughs in the fields of material science. The organic moieties distributed uniformly in the mesoporous framework will not block the pore, which is beneficial to the diffusion of guest molecule. The surface hydrophilicity/hydrophobicity, mechanical and hydrothermal stability of the PMOs could easily be tuned. The unique features of the PMOs make them attractive in many applications. The recent progresses in the synthesis, characterization and application of the PMOs are summarized, with special emphasis on their applications in catalysis, adsorption, separation, and photoelectricity. The future development of the PMOs is also prospected.